ANALYSIS OF SUSTAINABILITY REPORT DISCLOSURE, EXTERNAL ASSURANCE, ENVIRONMENTAL PERFORMANCE AND FINANCIAL ACCESS ON NON-FINANCIAL SECTOR COMPANIES - Geodita Woro Bramanti; Ninditya Nareswari; Maydawati Fidellia Gunawan; Aang Kunaifi; Nugroho Priyo Negoro; Berto Mulia Wibawa (UNUSA Press, 2021)
Economic growth in Indonesia is growing rapidly, this further exacerbates the current environmental conditions which are characterized by high levels of pollution, greenhouse gas effects, global warming and the threat of ecosystem extinction. The emergence of various environmental problems that occur today are caused by various sectors, one of which is the industrial sector. As the largest contributor to GDP in Indonesia, the industrial sector which is an IDX listing company has an obligation to have a sustainability report where this report describes economic, social and environmental activities. This sustainability report can provide information symmetry that can be considered by third parties, both financial institutions and investors. This sustainability report must have external quality and assurance so that it is not just a disclosure but can be a reliable sustainability report. Therefore, this study has an aim to analyze the relationship between the sustainability reports quality, the external assurance quality, usage of external assurance, environmental performance and financial access. The sample population are non-financial sector companies listed on the Indonesia Stock Exchange and PROPER during the 2014-2019 period. The analytical method used is panel data regression analysis using STATA.The result of this study found a significant strongly relationship between environmental performance and the quality of sustainability report disclosures on the company's financial access. In contrast, there is an insignificant effect between the quality of external assurance sustainability report disclosure on the financial access of the main sector and manufacturing companies.